2018
DOI: 10.1111/ijfs.14004
|View full text |Cite
|
Sign up to set email alerts
|

Improved function of bamboo shoot fibre by high‐speed shear dispersing combined with enzyme treatment

Abstract: Summary With the increase in global welfare, metabolic syndrome‐related diseases seriously disrupt our quality of life. Balanced diet with low calories, low glycaemic index, and high dietary fibre such as bamboo shoot fibre is needed. Functional properties of dietary fibre can be improved by processing methods. Therefore, we compared the effect of three processing methods (high‐speed shear dispersing, enzyme treatment and combined treatment) on the characteristics and functions of bamboo shoot fibres. Combined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…It has been reported that different extraction methods tend to result in different molecular weights, which can further affect the functional activity of SDF [ 37 ]. EE-SDF, MEE-SDF, and TPP-SDF showed two main peaks, in which the Mw value of the highest peak was 168.57, 9.28, and 2.66 kDa, and the peak area was 87.91%, 92.90%, and 86.10%, respectively ( Table 3 ), indicating that microwave treatment can facilitate the release of SDF with low molecular weights, which is similar to the effect of microwave treatment reported by Yang et al [ 38 ]. In addition, the TPP-SDF had lower Mw values than MEE- and EE-SDF, mainly because TPP extraction tends to result in low molecular weights of SDF.…”
Section: Resultssupporting
confidence: 83%
“…It has been reported that different extraction methods tend to result in different molecular weights, which can further affect the functional activity of SDF [ 37 ]. EE-SDF, MEE-SDF, and TPP-SDF showed two main peaks, in which the Mw value of the highest peak was 168.57, 9.28, and 2.66 kDa, and the peak area was 87.91%, 92.90%, and 86.10%, respectively ( Table 3 ), indicating that microwave treatment can facilitate the release of SDF with low molecular weights, which is similar to the effect of microwave treatment reported by Yang et al [ 38 ]. In addition, the TPP-SDF had lower Mw values than MEE- and EE-SDF, mainly because TPP extraction tends to result in low molecular weights of SDF.…”
Section: Resultssupporting
confidence: 83%
“…Nitrite ion adsorption capacity The methods described by Yang 19 and Zhang et al 23 were used to determine the nitrite ion adsorption capacity (NIAC) of the samples. First, 500 mg of sample was added to 25 mL of 100 μmol L −1 sodium nitrite solutions (pH 2.0 or 7.0) simulating the stomach and small intestine environments, and the mixtures were allowed to react at 37 °C for 2 h. Thereafter, the samples were centrifuged at 4000×g for 20 min and the supernatant was collected for subsequent testing.…”
Section: Bile Acid Binding Capacitymentioning
confidence: 99%
“…They are not only delicious but also therapeutically rich. Investigation of the juvenile shoots to understand its exceptional nutritional values and health benefits is already highlighted by numerous studies [8][9][10]. The outcomes showed that the shoots are rich in nutrients and massive health promoting compounds.…”
Section: Introductionmentioning
confidence: 99%